2022
DOI: 10.1371/journal.pcbi.1010171
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic management and control through risk-dependent individual contact interventions

Abstract: Testing, contact tracing, and isolation (TTI) is an epidemic management and control approach that is difficult to implement at scale because it relies on manual tracing of contacts. Exposure notification apps have been developed to digitally scale up TTI by harnessing contact data obtained from mobile devices; however, exposure notification apps provide users only with limited binary information when they have been directly exposed to a known infection source. Here we demonstrate a scalable improvement to TTI … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The normalization induced by Equation C1 also enables the use of isotropic regularization in Equations 25 and 26, even though the physical parameters ϕ may differ in order of magnitude. For more examples of parameter transformations in the context of EKI and UKI, see Huang, Schneider, and Stuart (2022), Schneider et al (2022), andDunbar et al (2022).…”
Section: Appendix A: Configuration-based Principal Component Analysismentioning
confidence: 99%
“…The normalization induced by Equation C1 also enables the use of isotropic regularization in Equations 25 and 26, even though the physical parameters ϕ may differ in order of magnitude. For more examples of parameter transformations in the context of EKI and UKI, see Huang, Schneider, and Stuart (2022), Schneider et al (2022), andDunbar et al (2022).…”
Section: Appendix A: Configuration-based Principal Component Analysismentioning
confidence: 99%
“…It does so by defining transformation maps under-the-hood from the constrained space to an unconstrained space where the optimization problem can be suitably defined. Constrained optimization using this framework has been successfully demonstrated in a variety of settings (Dunbar et al, 2022;Lopez-Gomez et al, 2022;Schneider, Dunbar, et al, 2022).…”
Section: Featuresmentioning
confidence: 99%
“…The EnKF, which we use to combine observation data with an age-structured model of overdose mortality, originated from research activities in the geophysical sciences and has found various applications in problems that require combining high-dimensional dynamical systems with observation data [ 25 ]. Kalman filtering and related data assimilation methods (e.g., Bayesian Markov chain Monte Carlo) have been used in computational biology and medicine to estimate model parameters [ 26 – 29 ], identify patients with antibiotic-resistant bacteria in hospital wards [ 30 ], and develop risk-dependent contact interventions in epidemic management [ 31 ]. Within computational social science, data assimilation methods have proven useful in combining mechanistic models with survey data, e.g., to study the evolution of political polarization in the United States [ 32 ].…”
Section: Introductionmentioning
confidence: 99%